2019
DOI: 10.1002/2050-7038.12015
|View full text |Cite
|
Sign up to set email alerts
|

How optimal PMU placement can mitigate cascading outages blackouts?

Abstract: Summary The conventional optimal PMU placement (OPP) methods minimize the number of PMUs along with guarantying full observability of the system. However, various OPP schemes with the same number of PMUs obtained for a power system have different performances in emergency conditions. Cascading outages as the major cause of recent large blackouts cancel out full observability of the system and decrease situational awareness. In this paper, the OPA model previously developed to simulate power system blackouts is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…46,48 In that case, the reliability of the measurement cannot be assured. To remove a fault, most of the time, the faulty line or bus is removed from the system.…”
Section: Solution Of Opp Considering Practical Contingencies-singlementioning
confidence: 99%
See 1 more Smart Citation
“…46,48 In that case, the reliability of the measurement cannot be assured. To remove a fault, most of the time, the faulty line or bus is removed from the system.…”
Section: Solution Of Opp Considering Practical Contingencies-singlementioning
confidence: 99%
“…The removal of any line or bus leads to loss of connectivity within the associated buses. 46,48 In that case, the reliability of the measurement cannot be assured. Some of the measurements may not available at all during these contingencies.…”
Section: Solution Of Opp Considering Practical Contingencies-singlementioning
confidence: 99%
“…Also, because OPPP is a combination optimization challenge, the authors have not shown several solutions. The author suggested a regular binary variant of the particle swarm optimization (BPSO) to identify the OPPP [24]. However, the traditional BPSO suffered from premature convergence and is stuck in local minima, particularly in complex combination problems.…”
Section: Introductionmentioning
confidence: 99%
“…OPPP solution for 57-bus system using DFS, GTP, SAM, RSNA, and MBBA ,7,9,15,19,21,24,27,30,32,36,38,39,41,46, 50, 52, 54 0.01 GTP 1 21 2, 4, 7, 9, 15, 16, 17, 19, 21, 24, 27, 30, 32, 36, 38, 39, 41, 46, 50, 52, 54 0.02 SAM 1 19 1, 4, 7, 9, 15, 19, 21, 24, 27, 30, 32, 36, 38, 39, 41, 46, 50, 52, 54 13.8 2 18 1, 4, 9, 13, 17, 19, 23, 27, 28, 30, 32, 39, 42, 44, 47, 50, 52, 54 15.3 3 18 1, 6, 12, 15, 16, 19, 23, 29, 30, 33, 34, 43, 44, 49, 50, 53, 55, 56 , 16, 17, 20, 25, 29, 32, 36, 41, 48, 51, 54 1.81 Abbreviations: DFS, depth-first search; GTP, graph-theoretic procedure; MBBA, modified branch-andbound algorithm; OPPP, optimal phasor measurement unit placement problem; PMU, phasor measurement unit; RSNA, recursive security N algorithm; SAM, simulated annealing method.…”
mentioning
confidence: 99%
“…This is a rigorous research area and a number of conference and journal papers have been published on OPP in some important journals (Refer Figure 1) during the past few decades. A stochastic model‐based method was proposed to differentiate between OPP schemes, which helps in analyzing the effect of OPP in mitigating cascading outages during blackouts 2 …”
Section: Introductionmentioning
confidence: 99%